The Impact of COVID-19 on Workers in Hawassa Industrial Park - World Bank (World Bank, Washington, DC, 2020)
As part of the World Bank Group’s analytical work program on More, better, and more inclusive jobs: Preparing for successful industrialization in Ethiopia (funded by the UK Department for International Development), a team of researchers led by Morgan Hardy (New York University Abu Dhabi) and Christian Johannes Meyer (University of Oxford) is deploying high-frequency phone surveys on a representative sample of garment factory workers in Hawassa Industrial Park (HIP) to document how their lives are changing during the Coronavirus Disease 2019 (COVID-19) crisis. This Rapid Briefing Note reports the preliminary baseline results from 3,163 female respondents, summarizing the more detailed “Living Paper” written by the team of researchers. The data collection took place between April 28 and May 26, 2020.